Environmental and Performance Assessment of Protective Outer Layers for Paper-Based Building Envelopes - Jasiołek Agata; Gromek Jagoda; Misiurka Szymon; Łątka Jerzy F. (Architecture, Civil Engineering, Environment)
Paper-based building components can lead towards more sustainable, energy-efficient, affordable structures. Building envelope is one of the most common areas for the application of paper in architecture. However, paper-based envelope requires an outer layer protecting it against water, fire and mechanical damages, which may significantly increase the components’ environmental impact, weight and manufacturing costs. The article review fourteen original outer layers design proposals, suitable for use on indoor, outdoor and roof surfaces. All the designs combine various protective materials and complementary coating techniques. The environmental impact of proposed designs is assessed via Life Cycle Assessment analysis based on Ecoinvent 3.8 database. The proposals’ performance is assessed in the areas of water, fire and mechanical damage protection, materials cost and availability. Designs with high-performance scores and low environmental impact are indicated for both indoor and outdoor applications. As a conclusion from the research, guidelines and suggestions for further development of paper-based building envelopes are provided.